ANALYSIS OF INDUSTRY TYPE, COMPANY BASIS AND MEDIA EXPOSURE TOWARD THE CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE IN MANUFACTURING COMPANIES ON REGISTERED IN INDONESIA STOCK EXCHANGE - DUMARIANI SILALAHI; HARLEN SILALAHI (JURNAL ILMIAH KOHESI, 2022)
This study uses annual financial report data in manufacturing companies listed on the Indonesia Stock Exchange in 2018. The total population was 168 companies. The research sample was 63 companies which were selected using proportional stratified random sampling. The purpose of this research is to analyze whether industry type, company basis, and media exposure, give some effects toward the Corporate Social Responsibility (CSR) disclosure in Manufacturing Companies on registered companies in Indonesia stock exchange The result shows that the industry type gives some effects toward the CSR disclosure. Company basis and media exposure do not give any effects toward the CSR disclosure.